Time, memory and class: The unintended consequences of the bourgeois gaze. (December 2018) - Lund, Anna
In this article, I argue that currently there is a middle-class bias that dominates in sociological culture and structures the ways the discipline operates as a form of bourgeois gaze. These forms of regulation and structuration within the discipline are also visible in Paul Willis's book Learning to Labour (1977), and they need to be illuminated, problematized and challenged if the discipline is to be able to contribute meaningfully and critically to an enlargement of its approach to sociological analysis, including the analysis of class and youth culture. My attempt is to make an exposure and reconsider Learning to Labour through the lens of time, memory and class, by performing an additional reading of the 'the lads' orientation toward different temporalities and conscious practices of memory work.